Perceptions of Generation Z Communities in Bandung City Towards Interest in Using Fintech Lending - HIDAYAT, Moch Rizqan Shiyam; NURUNNISHA, Gina Apriyani (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research aims to provide insights to online lending service providers, the government, and financial institutions to improve financial literacy and customize services according to Generation Z's needs and expectations. The focus is on exploring the factors influencing Generation Z's decision to utilize Fintech Lending, such as perceived ease of use, usefulness, and trust. This study uses a descriptive quantitative method to reveal Generation Z's tendency to respond to these digital financial products. It was found that factors such as intention to use, perceived ease of use, perceived usefulness, and trust significantly influence their interest in using Fintech Lending. The conclusions of this study provide insights for Fintech Lending service providers, government, and financial institutions to improve services and financial literacy that align with Generation Z's expectations and needs. This research uses a descriptive quantitative method with a sample of generation Z respondents in Bandung. The variables studied include intention to use, perceived convenience, usefulness, and trust in online loans. The results showed that these variables significantly influence Generation Z's interest in using online loans. The findings provide valuable insights for financial service providers to customize their products and services to be more appealing to generation Z.”